Cultural And Socioeconomic Barriers in Utilization of Dental Services: A Cross Sectional Questionnaire Based Study - Patel, Khyati H; Nair, Vivek S; Kalra, Dheeraj D; Shetty, Vittaldas (National Journal of Community Medicine, 2016)
Introduction: In our society, the psycho-social attitude of many people is directly or indirectly responsible for failure in approaching and accepting the dental treatment. This study will help in implicating changes in the current mindset of the society towards oral health. Material and Methods: A questionnaire including two sections will be administered to patients reporting to the Out Patient Department of the institute. Section A including demographic data and Section B containing 20 simple closed ended questions which will assess the general perspective and beliefs of the patients towards oral health. Results: A total of 450 questionnaires were distributed, out of which 404 were filled, returned and analyzed (response rate of 89.77%). Out of the 404 respondents, 232(57.4%) were males and 172(42.6%) females. The mean age of the respondents was 32.11±11.66 (range 13-70 years). The results highlighted that the people belonging to the lower socio-economic groups (Grade III, IV and V) according to the Kuppuswamy scale were more reluctant to get dental treatment due to cultural beliefs, myths and lack of knowledge about oral health care. Conclusion: This study helps us understand the socioeconomic barriers in accessing dental treatment. Especially help us improve oral health in individuals belonging to lower socioeconomic groups.